2022
DOI: 10.3389/fonc.2022.840410
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gene Signature of Tripartite Motif Family for Predicting the Prognosis in Kidney Renal Clear Cell Carcinoma and Its Association With Immune Cell Infiltration

Abstract: Given the importance of tripartite motif (TRIM) proteins in diverse cellular biological processes and that their dysregulation contributes to cancer progression, we constructed a robust TRIM family signature to stratify patients with kidney renal clear cell carcinoma (KIRC). Transcriptomic profiles and corresponding clinical information of KIRC patients were obtained from The Cancer Genome Atlas (TCGA) and the International Cancer Genome Consortium (ICGC) databases. Prognosis-related TRIM family genes were scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We recently developed a prognostic signature for clear cell renal cell carcinoma (ccRCC) using genes from the TRIM family. Additionally, we found that some TRIM proteins, such as TRIM26, had predictive value in ccRCC [ 36 ]. Nevertheless, the specific function of TRIM26 in ccRCC has not been previously documented.…”
Section: Discussionmentioning
confidence: 99%
“…We recently developed a prognostic signature for clear cell renal cell carcinoma (ccRCC) using genes from the TRIM family. Additionally, we found that some TRIM proteins, such as TRIM26, had predictive value in ccRCC [ 36 ]. Nevertheless, the specific function of TRIM26 in ccRCC has not been previously documented.…”
Section: Discussionmentioning
confidence: 99%
“…Thus lead to the diverse and even diametrically opposite cell function in cell proliferation and mitosis, immune response, tumorigenesis or harmonization of certain ubiquitination-related signal pathways [ 15 – 17 ]. Studies have verified that abnormal expression of TRIM family members were existed in multiple cancers [ 6 , 17 19 ], and effected the tumor cells by promoting epithelial mesenchymal transition (EMT) and aerobic glycolysis [ 20 ]. The TRIM family functioned in tumorigenesis based on their other non-classical domains.…”
Section: Discussionmentioning
confidence: 99%
“…A six hypoxia-related gene prognostic model was established to predict OS in patients with KIRC. Zheng et al [ 22 ]. Also established a similar prognostic model for KIRC patients via comprehensive analysis of tripartite motif (TRIM) proteins.…”
Section: Discussionmentioning
confidence: 99%